1973
DOI: 10.1136/bmj.4.5894.714
|View full text |Cite
|
Sign up to set email alerts
|

Histidine for Treatment of Uraemic Anaemia

Abstract: Summary A group of 28 uraemic patients on dialysis treatment were given daily supplements of histidine by mouth. Plasma amino-acid concentration, plasma iron, serum transferrin, packed cell volume, and reticulocyte count were all measured before and after two months of histidine supplementation. The treatment raised the plasma histidine concentration and at the same time there was a rise in transferrin and iron levels and packed cell volume. Reticulocyte counts fell after two months of histidine supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Anaemia associated with decreased HIS concentration in the blood has been repeatedly observed in patients with chronic kidney disease, particularly in patients undergoing dialysis [129,130]. Increased haematocrit values in HIS-supplemented patients with uraemia have been reported by Giordano et al [2]. However, the design of the study by Giordano and colleagues has been criticized by Phillips et al [131], and the results of 2 subsequent studies suggested that HIS supplementation did not improve anaemia in patients with uraemia [129,130].…”
Section: Anaemia Of Patients With Uraemiamentioning
confidence: 97%
See 1 more Smart Citation
“…Anaemia associated with decreased HIS concentration in the blood has been repeatedly observed in patients with chronic kidney disease, particularly in patients undergoing dialysis [129,130]. Increased haematocrit values in HIS-supplemented patients with uraemia have been reported by Giordano et al [2]. However, the design of the study by Giordano and colleagues has been criticized by Phillips et al [131], and the results of 2 subsequent studies suggested that HIS supplementation did not improve anaemia in patients with uraemia [129,130].…”
Section: Anaemia Of Patients With Uraemiamentioning
confidence: 97%
“…L-Histidine (HIS) is a nutritionally essential amino acid (EAA) with unique biochemical and physiological properties, which have created a good theoretical rationale to suggest the use of HIS as a nutritional supplement in a wide range of conditions. Initially, HIS was shown to treat rheumatoid arthritis and anaemia in patients with chronic renal failure [1,2]. Currently, HIS and/or HIS-containing dipeptides (HIS-CD) are investigated to prevent fatigue during strenuous exercise and for therapy in ageing-related disorders, metabolic syndrome, atopic dermatitis, ulcers, inflammatory bowel diseases, ocular diseases, and neurological disorders [3][4][5][6][7][8][9].…”
Section: Introduction and Aimsmentioning
confidence: 99%